The Textbook of Clinical Sexual Medicine - IsHak, Waguih William (Springer International Publishing : Imprint: Springer, 2017)
This textbook is a comprehensive resource covering sexual disorders in depth, from etiology, pathophysiology, phenomenology, treatment, to prognosis. The book highlights aspects the biological and psychosocial factors predisposing, precipitating, and perpetuating sexual dysfunction, and the importance of integrating biological and psychosocial treatments. Specialized chapters cover specific common medical complaints, including erectile, ejaculatory, and orgasmic disorders in the male; desire, arousal and orgasmic disorders in the female; and an integrated approach to the couple. With its focus on educational tools including over 100 figures, easy-to-use DSM-5 criteria table, and quick-guide appendices, this textbook is specially designed to educate readers on the psychiatric evaluation, treatment, and management of a wide range of sexual disorders. The Psychiatric Textbook of Sexual Medicine is a vital resource for medical students, residents, fellows, graduate students, psychiatrists, psychologists, women's health specialists, urologists, endocrinologists, general practitioners, social workers, and all medical professionals and trainees working with patients suffering from sexual disorders.